1979
DOI: 10.1042/bj1840491
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the rat liver microsomal enzyme system converting cholecalciferol into 25-hydroxycholecalciferol. Evidence for the participation of cytochrome p-450

Abstract: Properties of the rat hepatic cholecalciferol 25-hydroxylase have been studied. An assay system has been developed in which 25-hydroxycholecalciferol production is linear for at least 2h in both homogenates and microsomal fraction. Furthermore, the initial reaction velocity is linearly related to the amount of liver tissue or microsomal fraction. This enzyme system also metabolizes an analogue of cholecalciferol, namely dihydrotachysterol 3, into 25-hydroxydihydrotachysterol 3. The 25-hydroxylase is in the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(38 citation statements)
references
References 29 publications
0
35
0
3
Order By: Relevance
“…5B and 8B), the mitochondrial CYP27A1 enzyme was more active at higher concentrations of vitamin D 3 substrate than was CYP2R1. This behavior represents a third line of evidence in support of CYP2R1 being the microsomal vitamin D 25-hydroxylase because in vivo data (42) and in vitro data (10,17,44) suggest that the mitochondrial hydroxylase is a low affinity, high capacity enzyme, whereas the microsomal hydroxylase is a high affinity, low capacity enzyme. Although the reasons for these apparently different kinetic properties were not determined here, future experiments with the recombinant CYP27A1 and CYP2R1 enzymes should reveal whether they are related to transport of the vitamin into the mitochondrion or microsome, differences in the biochemical characteristics of the two enzymes, or other parameters.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…5B and 8B), the mitochondrial CYP27A1 enzyme was more active at higher concentrations of vitamin D 3 substrate than was CYP2R1. This behavior represents a third line of evidence in support of CYP2R1 being the microsomal vitamin D 25-hydroxylase because in vivo data (42) and in vitro data (10,17,44) suggest that the mitochondrial hydroxylase is a low affinity, high capacity enzyme, whereas the microsomal hydroxylase is a high affinity, low capacity enzyme. Although the reasons for these apparently different kinetic properties were not determined here, future experiments with the recombinant CYP27A1 and CYP2R1 enzymes should reveal whether they are related to transport of the vitamin into the mitochondrion or microsome, differences in the biochemical characteristics of the two enzymes, or other parameters.…”
Section: Resultsmentioning
confidence: 98%
“…Studies over the last 30 years identified vitamin D 25-hydroxylase activities in both microsomal (16,17) and mitochondrial membranes (10) that were associated with cytochrome P450 enzymes. Purification of the mitochondrial protein (12,13), and subsequent cDNA cloning (14,15,37), yielded the CYP27A1 sterol 27-hydroxylase, which, in addition to hydroxylating vitamin D, catalyzed 27-hydroxylation of sterol intermediates in the bile acid biosynthetic pathway (38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies indicated that 25-hydroxylase activity is present in both mitochondrial and microsomal subcellular fractions (25)(26)(27), and that the two enzymes exhibit different biochemical properties with respect to substrate affinity and capacity (28,29). The mitochondrial enzyme was purified (30,31), and after the cloning of its cDNA (32), revealed to be the CYP27A1 CYP that is also responsible for the 27-hydroxylation of sterol intermediates in bile acid synthesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that 25-hydroxylation is catalyzed by cytochrome P450 enzymes present in microsomes and mitochondria of liver (15,16). Until now, one mitochondrial and three microsomal cytochrome P450 enzymes have been reported as vitamin D 3 25-hydroxylases: CYP2C11 (17, 18), CYP2D25 (23,24), and CYP2R1 (25).…”
mentioning
confidence: 99%